Development of oleogel by structuring the blend of corn oil and sunflower oil with beeswax to replace margarine in cookies - Aqsa Zulfiqar; Muhammad Asim Shabbir; Fizza Tahir; Moazzam Rafiq Khan; Waqar Ahmed; Seydi Yıkmış; Muhammad Faisal Manzoor; Gholamreza Abdi; Rana Muhammad Aadil (Food Chemistry: X, 2024)
Oleogel significantly affects the product's sensory properties, texture, and shelf life. The goal of this study was to create oleogel by combining corn oil and sunflower oil and utilizing beeswax as a structural agent. A variety of physicochemical analyses were done to evaluate the quality of oleogel, including peroxide value, iodine value, saponification value, fatty acid, rheological parameters and firmness. Different percentages of oleogel, ranging from 0% to 75%, were used to substitute margarine in cookies. The cookies' quality was evaluated using proximate analysis, color analysis, texture analysis, calorific value, and sensory analysis. The study yielded substantial results by finding the ideal margarine-to-oleogel mix ratio, allowing for the manufacturing of high-quality cookies with a greater degree of unsaturation. Cookies with oleogel showed higher levels of unsaturation and better properties, making them the preferred option among consumers.